What Determines Protection of Property Rights? An Analysis of Direct and Indirect Effects - Ayyagari, Meghana; Demirgüç-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2012)
Using cross-country data, the authors evaluate historical determinants of protection of property rights. They examine four historical theories that focus on conceptually distinct causal variables believed to shape institutions: legal origin, endowments, ethnic diversity, and religion. There is only one realization of the data with relatively few observations, which have by now been well explored in the literature. Given the correlations between the explanatory variables, it is difficult to fashion empirical tests which are consistent in their treatment of the competing theories and to know which regressions to take seriously, giving rise to competing interpretations in the literature. The authors use Directed Acyclic Graph (DAG) methodology to identify which historical factors are direct determinants of property rights protection and which are not, and subject the outcomes to a battery of robustness tests. The empirical results support ethnic fractionalization as a robust determinant of property rights protection. Despite the attention it has received in the literature, the impact of legal origin on protection of property rights appears fragile and dependent on the inclusion of transition economies in the sample.